Arbitrariness and conventionality in polysemic Murut motifs / Nadia Mahmud - Mahmud, Nadia (2017)
The Murut ethnic group is one the earliest ethnic groups in Sabah. The traditional craftwork and attire of the Murut are decorated with motifs that are derived from figures (anthropomorphic and zoomorphic), floral and objects. Due to the inevitability of modern conveniences and technology, the knowledge of the denotation as well as connotation of the motifs are being threatened. In an effort to preserve the motifs, they have been constantly used not only in traditional medium but adapted to non-traditional medium as well. The message or themes presented in the visual composition of the motifs must be carefully regarded to avoid misinterpretation and cultural appropriation. This research aims to evaluate the conventionality of polysemic Murut motifs through determining the level of arbitrariness in the semiosis between the representamen and its object and interpretant. This study employed a mixed-method approach through semi-structured interviews with Murut representatives, a questionnaire survey with respondents with Art and Design backgrounds and a semiotic analysis of the motifs' structure and semiosis. The research discovered that the arbitrariness and conventionality of the object of the motifs were influenced by its motif type where motifs that represented human figures were the least arbitrary therefore the least conventional and motifs that represented animals were the most arbitrary and thus, highly conventional. The interpretants of the motifs were found to be generally accepted, despite some having their individual objects unidentifiable.